Mg/Ca and Sr/Ca as novel geochemical proxies for understanding sediment transport processes within coral reefs. (15th October 2017) - Gacutan, J.; Vila-Concejo, A.; Nothdurft, L.D.; Fellowes, T.E.; Cathey, H.E.; Opdyke, B.N.; Harris, D.L.; Hamylton, S.; Carvalho, R.C.; Byrne, M.; Webster, J.M.
Abstract: Sediment transport is a key driver of reef zonation and biodiversity, where an understanding of sediment dynamics gives insights into past reef processes and allows the prediction of geomorphic responses to changing environmental conditions. However, modal conditions within the back-reef seldom promote sediment transport, hence direct observation is inherently difficult. Large benthic foraminifera (LBF) have previously been employed as 'tracers' to infer sediment transport pathways on coral reefs, as their habitat is largely restricted to the algal flat and post-mortem, their calcium carbonate test is susceptible to sediment transport forces into the back-reef. Foraminiferal test abundance and post-depositional test alteration have been used as proxies for sediment transport, although the resolution of these measures becomes limited by low test abundance and the lack of variation within test alteration. Here we propose the novel use of elemental ratios as a proxy for sediment transport. Two species, Baculogypsina sphaerulata and Calcarina capricornia, were analysed using a taphonomic index within One Tree and Lady Musgrave reefs, Great Barrier Reef (Australia). Inductively coupled plasma-atomic emission spectrometry (ICP-AES) was used to determine Mg/Ca and Sr/Ca and these ratios were compared with taphonomic data. Decreases in test Mg/Ca accompany increases in Sr/Ca in specimens from algal-flat to lagoonal samples in both species, mirroring trends indicated by taphonomic values, therefore indicating a relationship with test alteration. To delineate mechanisms driving changes in elemental ratios, back-scattered electron (BSE) images, elemental mapping and in situ quantitative spot analyses by electron microprobe microanalysis (EPMA) using wavelength dispersive X-ray spectrometers (WDS) were performed on un-altered algal flat and heavily abraded tests for both species. EPMA analyses reveal heterogeneity in Mg/Ca between spines and the test wall, implying the loss of appendages results in a decrease in Mg/Ca. BSE imaging and WDS elemental mapping provided evidence for cementation, facilitated by microbial-boring as the primary cause of increasing Sr/Ca. These novel proxies hold advantages over taphonomic measures and further provide a rapid method to infer sediment transport pathways within back-reef environments. Graphical abstract: Highlights: Using Mg/Ca and Sr/Ca of large benthic foraminifera to successfully infer sediment transport pathways. The novel proxies overcome several limitations of traditional proxies. Physical and chemical forces may drive Mg/Ca trends, whilst differences in Sr/Ca driven by aragonite cementation.